Apelle, Ipponatte e la poetica di Eronda (Mim. 1 e 4) - Nicola Piacenza (Annali Online dell'Università di Ferrara. Sezione Lettere)
Starting from the assumption that the description of works of art in Herondas’ Mimiamb 4 (like the other ekphraseis in Theocritus, Posidippus or Apollonius) shows an important connection with the literary program of the poet, the article investigates in particular the affinity between Herondas and the official painter of Alexander the Great, Apelles, whose realistic accuracy in portraying everything was famous in antiquity. Herondas, like Apelles, was a victim of his enemies’envy. Furthermore, as Apelles seemed not to appreciate Antiphilus, a painter who invented the caricatures called “Grylloi”, so Herondas seems not to accept the caricatural element in his verses (the article offers a new allegorical interpretation of Gryllos in Mimiamb 1). Maybe the ancient poet Hipponax, another important model for Herondas, could have had the same attitude fighting against the sculptor Boupalos, who, according to the tradition, showed a comic figure of Hipponax himself to laugh.